Perforin Acts as an Immune Regulator to Prevent the Progression of NAFLD - Wang, Qian; Li, Dehai; Zhu, Jing; Zhang, Mingyue; Zhang, Hua; Cao, Guangchao; Zhu, Leqing; Shi, Qiping; Hao, Jianlei; Wen, Qiong; Liu, Zonghua; Yang, Hengwen; et al. (Frontiers in Immunology, 2020)
Nonalcohol fatty liver disease (NAFLD) is one of the main causes of cirrhosis and increases the risk of liver related death and hepatocellular carcinoma. Despite substantial clinical and basic research, the pathogenesis of obesity related NAFLD remains incompletely understood. Here we show that perforin can act as an immune regulator to prevent NAFLD progression. Aged perforin deficient mice (Prf-/-) mice have more lipid accumulation in liver than WT control. After feeding on high fat diet (HFD), Prf-/- mice show increased liver weight, more severe liver damage and inflammation when compared with WT controls. Mechanism studies substantiate that perforin specifically regulates intrinsic IFN- production from CD4 T cells, not CD8 T cells. CD4 T cells depletion relieves the liver injury, ameliorate the inflammation and metabolic morbidities in Prf-/- mice. What’s more, improved liver characteristics in HFD Prf-/-&IFN-R-/- double knockout mice confirmed IFN- as an important factor to mediate perforin-regulated NAFLD progression. Overall, our results discover the importance of perforin in regulating obesity related NAFLD, which provides novel therapeutic strategies of NAFLD.